2020
DOI: 10.1155/2020/1249829
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain Portfolio Selection with Borrowing Constraint and Background Risk

Abstract: Due to the complexity of financial markets, there exist situations where security returns and background factor returns are available mainly based on experts’ subjective beliefs, such as in the case of lack of historical data. To deal with such indeterminate quantities, uncertain variables are introduced. Based on uncertainty theory, this paper discusses the distribution function of the optimal portfolio return. Two types of new uncertain programming models, namely, the chance-mean model and the measure-mean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…However, profitability is the most important that affecting investment decision, followed by growth and trading volume (Lee, Huang, Chang, & Cheng, 2011). Dissimilarity to study through Lv, Zhang, Peng, & Ralescu (2020) is confirmed financial performance by considering background risk and asset liquidity does not effectively affect the investments made by investors in financial securities.…”
Section: Literature Reviewmentioning
confidence: 92%
“…However, profitability is the most important that affecting investment decision, followed by growth and trading volume (Lee, Huang, Chang, & Cheng, 2011). Dissimilarity to study through Lv, Zhang, Peng, & Ralescu (2020) is confirmed financial performance by considering background risk and asset liquidity does not effectively affect the investments made by investors in financial securities.…”
Section: Literature Reviewmentioning
confidence: 92%
“…In order to reflect different attitudes toward risk in one portfolio investment, Huang and Di [ 12 ] apply mental accounts to uncertain optimization model. Besides, there are uncertain portfolio optimization models considering the bankruptcy constraint [ 18 ], the borrowing constraint [ 24 ] and the entropy constraint [ 6 ]. Yet so far, no paper studies the EIT problem based on uncertainty theory.…”
Section: Introductionmentioning
confidence: 99%